2018
DOI: 10.1111/jch.13450
|View full text |Cite
|
Sign up to set email alerts
|

Paucity of high‐quality studies reporting on salt and health outcomes from the science of salt: A regularly updated systematic review of salt and health outcomes (April 2017 to March 2018)

Abstract: The purpose of this review is to identify, summarize, and critically appraise studies on dietary salt and health outcomes that were published from April 2017 to March 2018. The search strategy was adapted from a previous systematic review on dietary salt and health. Identified studies were screened based on a priori defined criteria to identify publications eligible for detailed critical appraisals. Overall, 6747 citations were identified by the search strategy, and 42 health outcome studies were identified. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 68 publications
1
6
0
Order By: Relevance
“…However, over one‐third of these studies were cross‐sectional (n = 10) and over half (n = 14) used low‐quality methods to assess sodium intake. The goal of the Science of Salt systematic reviews is to provide scientists, clinicians, and public health advocates with a regularly updated review of recent publications in the area of sodium and health outcomes, and only direct attention to studies that meet predefined criteria for outcomes assessed and methodology to assist in interpretation of this evidence base 10‐17 . In this field of study, poor methodological approaches have yielded results that contrast with evidence from studies using more rigorous methods 9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, over one‐third of these studies were cross‐sectional (n = 10) and over half (n = 14) used low‐quality methods to assess sodium intake. The goal of the Science of Salt systematic reviews is to provide scientists, clinicians, and public health advocates with a regularly updated review of recent publications in the area of sodium and health outcomes, and only direct attention to studies that meet predefined criteria for outcomes assessed and methodology to assist in interpretation of this evidence base 10‐17 . In this field of study, poor methodological approaches have yielded results that contrast with evidence from studies using more rigorous methods 9 .…”
Section: Discussionmentioning
confidence: 99%
“…To keep scientific, clinical, and policy stakeholders up to date with the quantity and quality of publications in the rapidly growing area of sodium and health outcomes, regularly updated reviews and critical appraisals are published in the Journal 10 . The objective of this eighth Science of Salt health outcomes review is to build on previous reviews in this series 11‐17 and summarize published articles on sodium and health outcomes from November 1, 2018, to August 31, 2019, and to highlight and critically appraise articles that meet pre‐specified methodological criteria 14 …”
Section: Introductionmentioning
confidence: 99%
“…Two important themes are highlighted by this review. Firstly, there remains a relatively small proportion of studies that meet our criteria for high‐quality studies, which was highlighted in our previous review . In particular, the use of inadequate sodium intake assessment in observational studies is problematic.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, there remains a relatively small proportion of studies that meet our criteria for high-quality studies, which was highlighted in our previous review. 50 In particular, the use of inadequate sodium intake assessment in observational studies is problematic. Six studies used spot urine collections to estimate usual sodium intake, 24,29,33,35,36,40 despite the large body of literature showing that spot urine collections lack precision and accuracy for assessment of usual sodium intake in individuals.…”
Section: Discussionmentioning
confidence: 99%
“…As part of this initiative, regularly updated systematic reviews on the relationship between salt and health outcomes, and the implementation of salt reduction interventions are being published in the Journal of Clinical Hypertension. 16 To date, 11 studies (six on the relationship of salt and health outcomes [17][18][19][20][21][22] and five related to the implementation of salt reduction interventions [23][24][25][26][27] ) have been published. The last implementation review was the first to employ a thematic approach focusing on studies that reported knowledge, attitudes, and behaviors relating to salt.…”
Section: Introductionmentioning
confidence: 99%